The effect of α-irradiation from enriched uranium on the leaching properties of PTFE. (April 2017) - Badenhorst, J.J.; Meyer, W.C.M.H.; van Rooyen, T.J.; Krieg, H.M.
Abstract: In the uranium enrichment plants of the South African Nuclear Energy Corporation SOC Ltd (Necsa), sintered polytetrafluoroethylene (PTFE) filters were used to remove gas entrained solid particles, in order to prevent blocking of the isotope separating elements. When these plants were decommissioned and dismantled, the filters which mostly contained solid uranium fluoride and uranium oxyfluoride compounds and compressor ring dust, were broken into pieces, put into metal drums, and stored. This waste contains enriched uranium and can't be disposed of at the current disposal site (Vaalputs), which only accepts low and intermediate level waste. Initial attempts, directly after removal from the enrichment plants, to decontaminate these filters using various aqueous solutions, were unsuccessful probably because of the known non-wettability of PTFE surfaces. However, recent attempts to leach the absorbed enriched uranium were successful. This resulted in a study to determine the effect of mainly α-irradiation from the enriched uranium on the morphology of PTFE. A Monte Carlo N-Particle transport code (MCNP), a general purpose radiation transport code modelling the interaction of radiation with materials that simulate nuclear processes, was used to determine the rate of PTFE radiolysis. The results confirmed that the dose rate received from mainly the α-particles (97%) during the storage period had caused significant structural damage to the PTFE depending on the enrichment grade and the amount of uranium on the filters. To confirm the modelling data, analytical techniques, including micro X-ray tomography, thermogravimetric analysis and X-ray diffraction were used to study the morphology changes in the PTFE structure of the research samples. Experimental results indicated that the crystallinity increased while the molecular weight of the PTFE decreased. This could be attributed to the radiation induced degradation of the PTFE by the absorbed enriched uranium. Highlights: In the uranium enrichment plants of the South African Nuclear Energy Corporation, (Necsa), sintered polytetrafluoroethylene (PTFE) filters were used to remove gas entrained solid particles. The filters contained enriched uranium fluoride and uranium oxy-fluoride compounds Initial attempts, directly after removal from the enrichment plants, to decontaminate these filters using various aqueous solutions, were unsuccessful however recent attempts to leach the absorbed enriched uranium were successful. This resulted in a study to determine the effect of mainly α-irradiation from the enriched uranium on the morphology of PTFE. A Monte Carlo N-Particle transport code (MCNP), a general purpose radiation transport code modelling the interaction of radiation with materials that simulate nuclear processes, was used to determine the rate of PTFE radiolysis. To confirm the modelling data, analytical techniques were used to study the morphology changes in the PTFE structure. Results indicated that the crystallinity increased while the molecular weight of the PTFE decreased which could be attributed to the radiation induced degradation of the PTFE by the absorbed enriched uranium.